Single‐atom catalyst application in distributed renewable energy conversion and storage. Issue 2 (2nd March 2023) - Li, Xiao; Xu, Wenxiu; Fang, Yuhan; Hu, Riming; Yu, Jiayuan; Liu, Hong; Zhou, Weijia
Abstract: In recent years, owing to the depletion of fossil energy and the aggravation of environmental pollution, the conversion and storage of distributed renewable energy (such as solar energy, wind energy, and tidal energy) based on electrochemical technology have attracted extensive attention. Electrocatalytic processes with high efficiency and high selectivity play a key role in clean energy conversion and storage. With the nearly 100% atomic utilization rate and unique catalytic activity, single‐atom catalysts (SACs) have been rapidly developed and widely used in the field of energy conversion and storage. In this review, we first introduce the characteristics of SACs. Then, we focus on the application of SACs in energy conversion, including water electrolysis reaction, nitrogen reduction reaction, nitrate reduction reaction, oxygen reduction reaction, and carbon dioxide reduction reaction. In terms of energy storage, we focus on supercapacitors and Li–S batteries. Further, we enumerate some of the methods for the synthesis of SACs in high metal loading or large scale. Finally, the main challenges and opportunities for this emerging field in the future are discussed and prospected. Abstract : The applications of single‐atom catalysts (SACs) in electrochemical energy conversion, including hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) of electrolytic water, the reduction reaction of nitrogen/nitrate (NRR/NO3 RR), oxygen reduction reaction (ORR), carbon dioxide reduction reaction (CO2 RR), and energy storage applications containing supercapacitors and batteries, are discussed in detail.